The representations of leadership by example in editorial cartoons Kepimpinan melalui melalui tauladan dalam kartun editorial - Embong, Rohani (Universiti Kebangsaan Malaysia Press, 2016)
Tun Dr Mahathir was the fourth Prime Minister of Malaysia, who was well known for his leadership values and major contributions to the country’s development. The dynamic and long career of Tun Dr Mahathir had given a lot of ideas and materials for Lat, a famous Malaysian cartoonist, in producing editorial cartoons with which Tun Dr Mahathir is the main character. Having said that, this paper thus aims to discuss the representations of Tun Dr Mahathir’s leadership in Lat’s editorial cartoons. The data for this study were 98 Lat’s editorial cartoons which were published in local newspapers from 1979 to 2004. The visual analysis was conducted using Multimodality, by which the represented leadership was determined through the identification of participants and process. Whilst the linguistics texts were analysed using Systemic Functional Linguistics focusing on the ideational messages. The findings of this study, among others, reveal that Tun Dr Mahathir was depicted as an open minded leader, who listened to others. Besides, Tun Dr Mahathir is also portrayed as a leader who kept abreast with the development of Information Communication Technology and hardworking. The aim of depicting the leadership values practiced by Tun Dr Mahathir in the editorial cartoons is to portray him as a leader who led by examples.